Vivaspin ultrafiltration: A new approach for high resolution measurements of colloidal and soluble iron species. (5th April 2013) - Schlosser, Christian; Streu, Peter; Croot, Peter L.
<x xml:space="preserve">Abstract</x> Vivaspin6® ultrafiltration units with molecular weight "cut‐off" membranes of 5, 10, 30, 50, and 100 kDa were used together to examine the size distribution of newly formed iron (Fe) colloids in natural seawater samples and in the presence of several different Fe chelators with varying Fe binding strength. Artificial Fe chelators, such as TAC, and 2 kDG, when added at equimolar levels to Fe, supported the formation of a continuum of Fe‐ligand colloids between 5 and 100 kDa. More than 90% of the added 55Fe in these solutions occurred in Fe aggregates/particles larger than 100 kDa. The strong siderophore DFO held the majority of the added 55Fe in the "truly" soluble fraction ≤ 5 kDa, whereas 90% of 55Fe added to UV‐irradiated seawater was converted into Fe colloids with a size between 50 to 100 kDa (5–6 nm). Membranes with ≥ 10 kDa showed similar "cut‐off" properties on natural seawater samples collected in the water column off the Peruvian coast. Fe solubility determined with these membranes was approximately six times greater than Fe solubility determined with the 5 kDa membrane and the 0.02 µm syringe filters. This suggests that a seamless size continuum of organic chelators (≤5 kDa‐10 kDa) is present in these seawaters and that estimates of ligand production based on 0.02 µm Anotop solubility experiments underestimates the abundance of soluble/colloidal ligands. Regarding these results, we recommend the use of Vivaspin 5 kDa membranes to separate the "truly" soluble from the colloidal Fe fraction.